Rothia mucilaginosa bacteremia: A 10‐year experience of a pediatric tertiary care cancer center. Issue 7 (1st March 2019) - Poyer, Fiona; Friesenbichler, Waltraud; Hutter, Caroline; Pichler, Herbert; Dworzak, Michael; Peters, Christina; Mann, Georg; Indra, Alexander; Attarbaschi, Andishe
Abstract: Rothia mucilaginosa is part of the oral and upper respiratory tract flora. Usually, this gram‐positive coccus is not pathogenic; however, in the setting of immunosuppressed hosts, it can cause life‐threatening infections as an opportunistic pathogen. Among a cohort of 1511 hematologic‐oncologic patients at a pediatric tertiary care cancer center, we identified five cancer patients (0.35%) within a period of 10 years having a proven Rothia mucilaginosa bacteremia (1 culture positive: n = 3/5; > 1 culture positive: n = 2/5). With prompt and adequate antibiotic treatment, infection resolved rapidly before recovery of neutrophils and without any sequelae, suggesting that Rothia mucilaginosa bacteremia without organ involvement is not exceptionally problematic in pediatric cancer patients.